Organizational Conflict New Insights - Fahed-Sreih, Josiane (IntechOpen, 2022)
This book is a collection of chapters on organizational conflict. It discusses the different types of conflict and how to deal with them. Whether it is a relationship conflict, task conflict, or process conflict, dealing with conflict requires analyzing the organization and its members and finding the root cause of the issue.